How do tanniferous forages influence soil processes in forage cropping systems?. Issue 1 (21st June 2022) - Clemensen, Andrea; Villalba, Juan J.; Lee, Stephen; Provenza, Frederick; Duke, Sarah; Reeve, Jennifer
Abstract: Nitrogen‐fixing legumes such as alfalfa ( Medicago sativa L.) and sainfoin ( Onobrychis viciifolia Scop.) may benefit agricultural systems. In addition to quality forage, both legumes contain secondary metabolites that play important roles in agroecological systems. Alfalfa contains triterpenes (saponins), and sainfoin contains phenolic compounds (tannins). Terpenes and phenolics can influence soil nutrient dynamics by inhibiting microbial activity, which could slow nitrogen mineralization and minimize nitrogen losses. However, research evaluating their influence in the soil has largely come from silviculture or laboratory studies. Therefore, we initiated a field study in Lewiston, UT, assessing how alfalfa and sainfoin influence soil characteristics. The randomized split‐plot block design had three replicates and included a fertilized bale‐and‐remove system, a green manure system (leaving mown plant forage in the field), and a no‐fertilizer bale‐and‐remove system. We measured saponin and condensed tannin (CT) concentrations in alfalfa and sainfoin, respectively, forage biomass, and soil characteristics [e.g., ammonium (NH4 ), nitrate (NO3 ), dehydrogenase, organic C, soil respiration, etc.]. Green manure plots showed greater microbial respiration ( p = .02), microbial biomass ( p < .01), and readily mineralized carbon ( p = .04) than other systems. Forage biomass was greater in sainfoin than in alfalfa ( p < .001), whereas soil NO3 was greater in alfalfa than in sainfoin ( p < .01). The soil NO3 differences could be explained by the inhibition of mineralization by CT in sainfoin compared with the saponins in alfalfa. Planting forages containing tannins may reduce nitrogen losses, thereby enhancing agricultural sustainability. Core Ideas: Plant secondary metabolites influence soil dynamics. Soil nitrate was greater in alfalfa than in sainfoin plots. Tannins from sainfoin may influence soil nitrogen cycling in forage cropping systems.